Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How do I calculate the infinite series:

$$\frac{1^2\cdot 2^2}{1!}+\frac{2^2\cdot 3^2}{2!}+\dots \quad?$$ I tried to find the nth term $t_n$.$$t_n=\frac{n^2\cdot (n+1)^2}{n!}.$$ So, $$\sum_{n=1}^{\infty}t_n=\sum_{n=1}^{\infty}\frac{n^4}{n!}+2\sum_{n=1}^{\infty}\frac{n^3}{n!}+\sum_{n=1}^{\infty}\frac{n^2}{n!}$$ after expanding. But I do not know what to do next.


share|cite|improve this question
One approach, not necessarily best, is to cancel n, then split remaining n as (n-1)+1 and cancel n-1, and keep going (paying attention to the beginning of the series). You get some integers and some e. – user31373 Jul 18 '12 at 3:19
We can write $$ n^2(n+1)^2 = an + bn(n-1) + cn(n-1)(n-2) + dn(n-1)(n-2)(n-3). $$ Comparing coefficients yields $$a = 4, \quad b = 14, \quad c = 8, \quad d = 1.$$ Then the rest is clear, yielding $$ \sum_{n=1}^{\infty} \frac{n^2(n+1)^2}{n!} = (a+b+c+d)e = 27e. $$ – Sangchul Lee Jul 18 '12 at 3:20
Look up Dobiński's Formula. – J. M. Jul 18 '12 at 3:32
@sos440 I like your method much. – Lingqiao Jul 18 '12 at 3:41
up vote 0 down vote accepted

You are right, now you need to expand them separately and express each of them in form of $e$:

$$ \sum \limits_{n=1}^{\infty}\frac{n^2}{n!}= \sum \limits_{n=1}^{\infty} \frac{n+(n-1)n}{n!} = \sum \limits_{n=1}^{\infty} \frac 1{(n-1)!} +\frac 1{(n-2)!} = 2e $$

Similarly, we can show that,

$$\sum \limits_{n=1}^{\infty}\frac{n^3}{n!}= \sum \limits_{n=1}^{\infty} \frac{n+(n^2-1)n}{n!} = 5e$$


$$\sum \limits_{n=1}^{\infty}\frac{n^4}{n!}= 15e$$

share|cite|improve this answer
thanks.I like this method. – Lingqiao Jul 18 '12 at 3:40

Given that $P(x)$ is a polynomial of degree $n$, we have $$P(x)=\sum_{k=0}^n\binom xk\Delta^kP(0)$$ which is Newton's series. Therefore \begin{align} \sum_{m\ge0}\frac{P(m)}{m!}&=\sum_{m\ge0}\sum_{k=0}^n\frac{\Delta^kP(0)}{k!(m-k)!}\\ &=\sum_{k=0}^n\frac{\Delta^kP(0)}{k!}\sum_{m\ge k}\frac1{(m-k)!}\\ &=e\sum_{k=0}^n\frac{\Delta^kP(0)}{k!} \end{align}

share|cite|improve this answer

The forms of the power series, you reached in the last step of your work, are known as Bell numbers. Bell numbers are defined as:

$$ B_{m} = \frac{1}{e}\,\sum_{n=0}^{\infty} \frac{n^m}{n!} $$.

So your result can be written in terms of Bell numbers:

$$ e( B_{4} + 2\,B_{3} + B_{2})\,, $$

where $ B_{4}=15 \,, B_{3}=5\,, B_{2}=2\,. $ See here.

share|cite|improve this answer

$$ t_n = \frac{4}{n!} \left( \frac{n(n+1)} {2} \right)^2 $$

share|cite|improve this answer
tn = (4/n!)[n(n+1)/2]^2 – Rajesh K Singh Jul 18 '12 at 8:29

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.